Stakeholder engagement in sustainability transitions - Gonzalez-Porras, Lara (Edward Elgar Publishing, 2021)
This chapter examines how stakeholder engagement can support sustainability transitions in society. We analyze 37 scholarly articles from the relevant literature, published from 2000 to 2020, to explicate the key assumptions and characteristics of stakeholder engagement in sustainability transitions. Our analysis identifies and focuses on four levels of stakeholder engagement: the individual level, the firm level, the industry level and the societal level. We show that stakeholder engagement in sustainability transitions can be understood as a relational, multi-level process that require continuous stakeholder collaboration. We conclude that, in addition to approaching stakeholders as change agents, stakeholder engagement as a relational process can be understood as providing change agency in sustainability transitions. Finally, we suggest pathways for future research on stakeholder engagement in sustainability transitions.